Perforated Weir for Effective Operation â€“ A Study - Gunjalli, Gowthami; S, Aishwarya; D, Muthu; Subramaniam C, Venkata; K, Ramakrishnan (International Journal of Engineering and Technology, 2018)
The excess water during monsoon season in the river is retained using low dams and it overflows through weirs. Maintaining the water depth at the required level and increasing the discharge from the weir are the current problems facing now a days. To overcome these problems, a novel sharp crested perforated weir has been developed in this work with different shapes of perforations viz. circle, rectangle, square and triangle having same area of perforation. A total of 24 models were made with single, double, triple opening for each shape, under two different sets of area of openings. The models were examined in a hydraulic tilting flume by keeping the discharge as constant. The variation in head obtained from these perforated weirs for different shapes were compared with a control weir which is a sharp crested rectangular weir. The expected theoretical discharge from these perforated weirs is compared with the actual discharge obtained. The values of coefficient of discharge for different perforated weirs were obtained by minimizing the error and the effective perforated weir is arrived by analyzing the values. This solution can be applied in solving practical problems.Â Â